The Prognostic and Immunotherapeutic Significance of AHSA1 in Pan-Cancer, and Its Relationship With the Proliferation and Metastasis of Hepatocellular Carcinoma - Li, Wenli; Liu, Jun (Frontiers in Immunology, 2022)
Abstract: The AHSA1 is a main activator of ATPase of Hsp90. Hsp90 is involved in various metabolic and developmental processes of tumor cells. Although, the role of AHSA1 in tumor cells is still unrecognized. In the current research, the RNA-seq of 33 tumors were downloaded using The Cancer Genome Atlas (TCGA) database for the analysis of AHSA1 expression in tumors. The Kaplan-Meier method was used for the evaluation of the prognostic significance of AHSA1 in patients with pan-cancer. Additionally, the correlation between AHSA1 and immune cell infiltration, immune checkpoint, pyroptosis-related molecules, epithelial cell transformation-related molecules, and autophagy-related molecules were analyzed by co-expression. Furthermore, we examined the effect of AHSA1 knockdown on cell function in Huh7 and HCCLM3 cells of hepatocellular carcinoma (HCC) cell lines. According to the finding of this study, up-regulation of AHSA1 expression was observed in numerous tumor tissues, and its over-expression in liver hepatocellular carcinoma (LIHC), lung adenocarcinoma (LUAD), and esophageal carcinoma (ESCA) could affect the overall survival and disease-specific survival of the patients. Meanwhile, as per the correlation analysis the expression of AHSA1 was greatly correlated with the expression of various immune cell infiltrates, immune checkpoint inhibitors, tumor mutation load, and microsatellite instability. Moreover, this study focused on analyzing the association of AHSA1 expression with multiple pathological stages in HCC, and confirmed that AHSA1 was an independent prognostic factor of HCC by univariate and multivariate COX regression in TCGA and The International Cancer Genome Consortium (ICGC) cohorts. At the same time, cellular experiments proved that the AHSA1 knockdown could decrease the proliferation activity, cell migration and invasion ability of HCC cells. Therefore, the results of this study indicated that AHSA1 can be used as a potential prognostic biomarker of tumors and it may have a significant role in the proliferation as well as migration of HCC cells.